2004
DOI: 10.1002/aoc.763
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a ferrofluid‐supported linear electrical machine

Abstract: The force magnification of ferrofluids used in the airgap between the two acting magnets in electrical machines has been investigated with the theoretical method of orthogonal expansion. This theoretical substantiation is necessary for a comprehensive judgement of the measurements on a ferrofluidsupported electric motor. The method itself and the results are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Based on this definition, the devices that use magnetofluidic composites (magnetizable nanofluids, MR suspension or/and MR suspensions in a mixture with magnetizable nanofluids) are called magnetofluidic devices. In his master's dissertation [134], Montoya carried out an interesting study concerning a modification of the magnetization of nanofluids based on ferrite nanoparticles, showing that the pressure variation D p in a magnetic field with a constant intensity H, is given by the variation DM of magnetization with temperature as follows: [135] and achieve linear motors [136,137]. The models developed in these studies showed that the use of magnetizable nanofluids with low viscosities leads to significant improvement in the electrical properties of steady current electric motors and high-efficiency linear motors.…”
Section: Magnetofluidic Devicementioning
confidence: 99%
“…Based on this definition, the devices that use magnetofluidic composites (magnetizable nanofluids, MR suspension or/and MR suspensions in a mixture with magnetizable nanofluids) are called magnetofluidic devices. In his master's dissertation [134], Montoya carried out an interesting study concerning a modification of the magnetization of nanofluids based on ferrite nanoparticles, showing that the pressure variation D p in a magnetic field with a constant intensity H, is given by the variation DM of magnetization with temperature as follows: [135] and achieve linear motors [136,137]. The models developed in these studies showed that the use of magnetizable nanofluids with low viscosities leads to significant improvement in the electrical properties of steady current electric motors and high-efficiency linear motors.…”
Section: Magnetofluidic Devicementioning
confidence: 99%
“…A remarkable force amplification in linear or rotating electric machines is predicted on account of theoretical investigations by filling the airgap between the acting magnets (stator, rotor) with a ferrofluid [1]. These calculations and experimental verifications in the case of a linear electric motor are presented here.…”
Section: Introductionmentioning
confidence: 95%
“…The coefficients of these series are found by matching the boundary conditions of field strengths between the rectangular or rotational symmetric subspaces, into which the whole area of investigation is divided. A more detailed explanation of the method of orthogonal expansion is given in [2].…”
Section: Magnetic Forces Calculated By Field Theorymentioning
confidence: 99%